Design of a Biomass Waste Shredding Machine Using the Quality Function Deployment (QFD) Method - Silma, Muhammad; Fiatno, Aris; Musridho, R. Joko; Sianturi, Gabriel; Henny, Henny; Setiawan, Benny; Tanjung, Lailatul Syifa (2477 - 6165, 2025)
This research aims to design a biomass waste shredder using the Quality Function Deployment (QFD) method to create a product that aligns with the needs and desires of users. The QFD method is employed to identify user requirements, translate them into technical specifications, and produce an optimal product design. The study involved 20 respondents from the Universitas Pahlawan Botanical Garden team as subjects to collect data on needs through closed questionnaires. The results indicate that consumers desire a shredder with key criteria, including speeding up the shredding process, high durability, safety in use, as well as ease of mobility and storage. The designed shredder product features several advantages, such as: An inlet feeder for biomass waste, six cutting blades with a bolt system, wheels for easy transportation. Through the House of Quality (HOQ) matrix, consumer needs were successfully translated into priorities for the development of the product's technical features. Compared to other shredders, this shredder has competitive advantages in functional aspects, user safety, and design. This demonstrates that the application of the QFD method is effective in producing an innovative, functional shredder design that meets user preferences. The findings of this study are expected to serve as a reference for the future development of shredder products.